Adoption of robotics in the TV film industry: The IoT-enabled robotic camera dolly - Hajjaj S.S.H.; Karim N.K.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Agricultural robots; Cameras; Entertainment industry; Industrial robots; Internet of things; Robotics; Film production; Financial impacts; Internet of Things (IOT); Interview protocols; Positive feelings; Remote operation; Robotic cameras; TV stations; Social robots